Przysłowie jako językowy nośnik wartości – perspektywa pedagogiczna - Kuszak, Kinga (Wydawnictwo Naukowe UAM, 2013)
This article looks at the values represented in traditional proverbs. The first part presents selected approaches to values, referencing the theories of M. Scheler, R. Ingarden, C. Kluckhohn, M. Nowak, and J. Puzynina. The following section examines the role of language as an instrument of verbalisation and introduction into the world of values. Referring to J. Bartmiński’s approach, it details the relations between language and the world of values. Subsequently, the article analyses the references to values and value judgements present in traditional Polish proverbs included in available reference works and studies. Taking as her starting point the definition of the term “proverb” and the oldest Polish proverbs preserved in writing, the author analyses proverbs used in the Polish language, focusing on those referring to values such as good, work, industriousness, happiness, luck, wisdom, and virtue. In this part of her study, she attempts to categorise the specific groups of proverbs, illustrating them with selected examples. The last part of the article addresses contemporary approaches to popular proverbs referencing values and value judgements, in particular the use of proverbs in advertising and the role of the verbal messages conveyed through advertising slogans. Presented are selected examples of advertisements and commercials related to values and value judgements which form the basis for the creation of new sayings that become part of contemporary Polish linguistic culture. Moreover, the author attempts to outline the manner in which new sayings are created, pointing out the fact that a significant number of them comes from advertising. The final part summarises the ways of a practical use of traditional proverbs.
Proverbs as carriers of linguistic value – a pedagogical perspective
Keywords: proverbs; tradition; values; language; language competences; linguistic worldview; linguistic representation of values; advertising